Risk Mapping and Shariah Compliance at BPRS Mitra Syariah Mandiri - Arman Jaya Ndruru; Masneni Laia; Nofatrio Soarota Zebua; Nabilla Nahda Maliha Samudra; Gunawan Syahputra Siburian; Meigia Nidya Sari (International Journal of Economic Research and Financial Accounting, 2025)
This study aims to explore and analyze the complexity of internal audit implementation in Islamic financial institutions, with the main focus on the Sharia People's Financing Bank (BPRS) Mitra Syariah Mandiri. This study was conducted through a comprehensive investigative approach throughout 2024, which includes collecting transaction data and evaluating existing operational mechanisms. In the audit process, the team managed to identify 276 critical transactions, with a total transaction value reaching IDR 45,250,000,000. The findings of the audit show that 94.2% of all transactions analyzed have met the rules and principles of sharia, with a contract structure that is in accordance with the provisions applicable in Islamic economic law. However, there are 5.8% of transactions that require in- depth improvements, especially in the aspect of the contract mechanism that needs to be adjusted to be more in line with the established sharia principles. This study also highlights the importance of the role of sharia audit in maintaining the compliance and integrity of Islamic financial institutions, especially in identifying potential risks and deviations that can harm institutions and customers. In addition, this study provides recommendations related to the need to improve internal systems and procedures to minimize transactions that are not in accordance with sharia provisions, as well as the importance of increasing human resource capacity in the field of sharia audit to support more effective supervision.